ROTOR STRENGTH ANALYSIS AND LIFE CALCULATION OF HEV MOTOR - DENG ChengHao; LIU WeiGuo; LI ZongHua; ZHOU AnJian; SU LinKe (Jixie qiangdu)
The interference fit between HEV motor rotor shaft and dynamo sheets was discussed in this paper. Assembly stress was analyzed and fatigue life was predicted by CAE method to study the motor rotor’s structural reliability. Comparison with the Von Mises stress results under different assembling methods shows,proper use of interference fit can reduce the stress fluctuation of matching components in deferent rotational speeds. Deeply research proves that interference fit in rotational part’s radial direction can obviously improve the fatigue performance if high stress fluctuation caused by centrifugal force exists.